Robust bioactive protein-based screws with dual crosslinked network for internal bone fixation. (1st June 2022) - Zhang, Qi-Chen; Ding, Wang; Ding, Sheng-Long; Meng, Qing-Bing; Su, Di-Han; Zhang, Tai-Wei; Chen, Qing; Lian, Rui-Xian; Zhao, Ming-Dong; Yu, Bao-Qing; Li, Xi-Lei; Li, Yu-Lin; et al.
Abstract: Resorbable fixation systems have gained interest in orthopedics by avoiding secondary surgery and stress shielding, but lack of enough bioactivity. Herein, we fabricated resorbable and bioactive regenerated silk fibroin/gelatin (RSF/G) screws with dual physically and chemically crosslinked networks, which can control the release of Arg-Gly-Asp (RGD) peptide and bear pull-out and shear forces comparable to those of pure RSF and commercial poly (lactic-co-glycolic acid) devices under dry and wet conditions. The controllable swelling properties of the RSF/G screws support implantation although with the high hydrophilic gelatin. Compared to RSF screws, the RSF/G screws have better bioactivity and significantly promote cell proliferation, adhesion, spreading and osteogenic differentiation by RGD-integrin interactions via the focal adhesion kinase/extracellular signal-regulated (FAK/ERK) pathway. Eight weeks after implantation in rats, the RSF/G screws with magnetic resonance imaging(MRI) compatibility remained fixed with tight contact, less inflammatory reaction and more new bone formation compared with pure RSF screws. The results indicate great promise for the application of RSF/G screws in bone fracture fixation. Highlights: A double-crosslinked silk fibroin/gelatin (RSF/G) screw was fabricated with limited swelling and sufficient strength. The RSF/G screws showed good biocompatibility and bioactivity for bone regeneration by RGD-integrin interactions. The screws could promote bone formation with less inflammatory reaction in the rat femoral condyles.